“The Early Years are Like a Foundation for the Future” Perspectives, Facilitators, and Challenges of Anganwadi Workers in Supporting Early Child Development Interventions in Hyderabad, India: Qualitative Findings from a Scalable Program Incorporating Early Child Development Interventions - Gitanjali Lall; Reetabrata Roy; Kunduru Sharath Chandrika; Gauri Divan (Indian Journal of Public Health)
Background: Integrated Child Development Services (ICDS) scheme, a large public health program, addresses the needs of young children with Anganwadi Workers (AWWs) as frontline agents of delivery. A scalable program incorporating early child development interventions (ASPIRE) has been developed to complement the program and address some of its gaps. Objectives: This paper describes formative work done with AWWs, as part of ASPIRE to assess their understanding of early childhood development (ECD) and acceptability of a novel ECD intervention using digital technology. Materials and Methods: Six focus group discussions (FGDs) were conducted with 31 AWWs, using a semi-structured guide. Results: Framework analysis of their responses from FGDs led to the identification of three themes: (1) time use, (2) understanding of ECD, and (3) delivering messages using videos. The findings suggest that AWWs tight schedules often leave them feeling overburdened with work. They are aware of factors that can aid as well as hinder child growth and development, but their understanding of play is limited to games played by older children. They expressed acceptability in using a video intervention, specifying features that would increase relevance for families. Conclusion: Integration of novel ECD interventions delivered by frontline workers needs to take into account their existing work schedules and associated challenges. Training on ECD interventions will need to broaden AWWs understanding of the critical foundational experiences which responsive caregiving and early child stimulation can provide.